Implementasi Pemenuhan Hak Anak pada Keluarga Menengah ke Bawah Pasca Cerai (Studi di Desa Kepuh, Kec. Kertosono, Kab. Nganjuk) - Binti Ni’matul Mufarrichah; Mufidah (Kartika: Jurnal Studi Keislaman, 2026)
Divorce in the family not only has an impact on the relationship between husband and wife, but also affects the fulfillment of children's rights, especially in lower-middle class families. After divorce, children often experience a lack of fulfillment of rights in the form of alimony, education, parenting, affection, and emotional attention. This condition shows that there is a gap between the provisions of Islamic law and positive Indonesian law and the reality in society. This study aims to determine the implementation of the fulfillment of children's rights after divorce in lower-middle and middle families in Kepuh Village based on the perspective of Islamic law and positive Indonesian law. This study uses a qualitative method with an empirical approach through interviews, observations, and documentation, then analyzed descriptively. The results of the study show that the fulfillment of children's rights after divorce is still not optimal because the needs of children are mostly met by mothers or close families, while some fathers have not fully carried out their obligations. Factors that affect these conditions include economic limitations, low parental responsibility, lack of legal understanding, post-divorce conflicts, infidelity, domestic violence, and remarriage. In the perspective of Islamic law and positive Indonesian law, both parents are still obliged to fulfill the rights of the child even after a divorce.